Motor dysfunction influence on executive functioning in manifest and premanifest Huntington's disease. Issue 3 (5th February 2014) - Hart, Ellen P.; Dumas, Eve M.; Schoonderbeek, Anne; Wolthuis, Shalane C.; van Zwet, Erik W.; Roos, Raymund A.C.
ABSTRACT: Motor disturbances can be present in both manifest and premanifest Huntington's disease (HD). We aimed to investigate the role of motor functioning on executive functioning to better understand the progression of cognitive dysfunction in HD. Forty patients with manifest HD, 21 patients with premanifest HD, and a group of 28 controls were tested twice with a 1‐year interval. For the Symbol Digit Modalities Test and the Figure Fluency Test, extra conditions were designed to measure motor involvement. Subtraction of this motor score from the original test score resulted in isolation of the cognitive component. Groups were compared on motor, cognitive, and original test scores using multilevel regression analysis. Manifest patients had lower baseline scores of 0.53 standard deviations (SD) on the original Symbol Digit Modalities Test ( P = 0.03) and 0.71 SD on the motor isolation part ( P = 0.006), and they showed a deterioration of 0.47 SD over 1 year of follow‐up on the original Symbol Digit Modalities Test ( P = 0.001) compared with controls. Premanifest patients had lower baseline scores of 0.67 SD on the Symbol Digit Modalities motor part ( P = 0.008) and deterioration of 0.48 SD on the original ( P = 0.001) and cognitive isolation ( P = 0.02) parts. Secondary analyses revealed that the premanifest deterioration resulted from the close‐to‐predicted‐onset group. Motor disturbances have a negative influence on performance on the Symbol Digit Modalities Test. Isolation of the cognitive component of this test revealed cognitive deterioration in the premanifest group only, caused by deteriorating scores for patients who were close to their predicted clinical disease onset. The Figure Fluency Test did not prove sensitive to cognitive change. © 2014 International Parkinson and Movement Disorder Society